Le Slesvig Holstein (1863-1864). L'agitation Lassallienne (1865) - Marx, Karl; Engels, Friedrich (Paris : Alfred Costes, 1934)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Lassalle, Ferdinand; Pruisen; Oostenrijk